Analysis of Women in the “Bangsal Isolasi” Film (Sara Mills Critical Discourse Analysis) - Mintana, Hans Hermang; Burhamudia, Irsyad (Sean Institute, 2025)
Gender injustice and violence against women is still a problem throughout the world and globally, including in Indonesia, where it is also reflected in various existing media, especially films. In the film Isolation Ward directed by Adhe Dharmastriya, it discusses the form of gender injustice that exists against women in a special prison for women and how both are in the position of perpetrators and victims of injustice and gender violence in a prison, especially a women's prison. This research aims to analyze the depiction of women's position in the film through Sara Mills' Critical Discourse Analysis approach, focusing on the position of subjects, objects and power relations formed. The research method in this study is descriptive qualitative with primary data in the form of film scenes and dialogs and sender data from related literature. The results showed four main depictions: (1) women's struggle to obtain information and justice; (2) violence against women; (3) exploitation of women; and (4) violence among women. The findings reveal how the movie reproduces gender injustice while offering a narrative of resistance through the main character, Wenny. In conclusion, the movie Isolation Ward not only reflects social reality but also becomes a media criticism of the patriarchal system and gender-based violence.